Legal Consequences of Authentic Deed Made by Notary after Declared Bankruptcy - Dian Nita NurJanah (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
AbstractThis research aims to analyze legal consequences of an authentic deed by Notary after being declared bankruptcy. The research method used is juridical normative. The data source is secondary data. The data analysis method used qualitative nomative. The result of this research are normatively in the Law of Notary Position that Notary declared bankrupt based on court decision that has obtained permanent legal force will dishonorable dismissal. A Notary is decraled bankrupt has legal consequences against the deed the made to lose authenticity. So, the authentic deed only has strenght evidence the private deed.Keywords: Notary; Legal consequences; Authentic; bankruptcy.